A novel approach for analysis of firm-level innovation strategies - Altuntas, Fatma (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThe determination of innovation strategy in companies is one of the most crucial activities to be conducted to achieve the company's vision. Determining the innovation strategy also reveals the innovation roadmap that needs to be followed for the company to reach its vision. The aim of this study is to propose a novel approach for the analysis of firm-level innovation strategies, namely the Corporate Innovation Strategy Determination Model (CISDM).Design/methodology/approachThe proposed approach considers each product group produced in the company and calculates gaps corresponding to product groups. The CISDM determines the innovation strategies for each product according to the required/expected and current situation for each type of innovation. The CISDM considers the dominant type of innovation implemented for each product group based on R&D performance in practice. To show how the CISDM works in practice, a real-life case study is conducted in a company for analysis of firm-level textile innovation strategies.FindingsTo show how the CISDM works in practice, a real-life case study is conducted in a company for analysis of firm-level textile innovation strategies. The CISDM is straightforwardly accepted and adopted in the implemented company due to the simple and practical applicability of the proposed approach. The result of the application of the proposed approach shows that it can easily be used for companies operating at every scale in the manufacturing industry.Originality/valueThere is no specific tool developed in the literature that systematically determines the innovation strategy of companies based on objective criteria. To fill this significant gap in the literature, a novel structured approach is proposed to determine innovation strategies of a company in this study. The proposed approach is called the CISDM.
Keywords: Innovation strategy; Textile industry; Product group analysis; Firm-level innovation; GREEN INNOVATION; RESOURCE-MANAGEMENT; MARKET ORIENTATION; PERFORMANCE; PRODUCT; IMPLEMENTATION; PROPOSAL; Business & Economics